Plastic buckling of a plate in shear - Hemp, W. S. (College of Aeronautics, 1957)
This note derives the mathematical equations for the analysis of the shear buckling of a plate, in the case where the initial stresses exceed the elastic limit of the material. It is hoped at a later stage to apply this theory to test results, which are being obtained using rectangular torsion boxes.